3D printing of biopolymer nanocomposites for tissue engineering: Nanomaterials, processing and structure-function relation. (December 2019) - Hassan, Mahbub; Dave, Khyati; Chandrawati, Rona; Dehghani, Fariba; Gomes, Vincent G.
Graphical abstract: Abstract: The inclusion of nanomaterials into biopolymeric matrices followed by three-dimensional printing is poised to open new horizons in tissue engineering by generating customized 3D structures with optimized properties and multifunctionality. In this review, we present an overview on nanostructured ceramic, metal, carbon and polymer materials integrated with hard and soft forms of biopolymers for manufacturing both acellular and cellular 3D tissue constructs using a range of 3D-printing and bioprinting techniques. Property enhancements and emergence of new functional characteristics of biopolymeric composites with the incorporation of nanomaterials, followed by 3D printing are of particular interest. Several methods, including fused deposition modelling, stereolithography, selective laser sintering and bioprinting using droplet, laser and extrusion assisted techniques are presented. Significant modifications via surface functionalization, biodegradation of scaffolds and the cytotoxicity of nanocomposites are discussed. The results derived from in vitro and in vivo analysis of stem cells and 3D printed scaffolds, their interactions and degradations are highlighted. Advances with multiple nanomaterials are also discussed with the advantages of harnessing the potential of 3D printing to produce unique multifunctional nanocomposites for tissue engineering.